2004
DOI: 10.1111/j.1742-4658.2004.04499.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of native peptides as potent inhibitors of enzymes

Abstract: Chymotrypsin is a prominent member of the family of serine proteases. The present studies demonstrate the presence of a native fragment containing 14 residues from Ile16 to Trp29 in a-chymotrypsin that binds to chymotrypsin at the active site with an exceptionally high affinity of 2.7 ± 0.3 · 10 )11 m and thus works as a highly potent competitive inhibitor. The commercially available a-chymotrypsin was processed through a three phase partitioning system (TPP). The treated enzyme showed considerably enhanced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Peptides regulate a variety of biological processes by acting as competitive inhibitors (Singh, et al, 2005), allosteric regulators (Lockless and Ranganathan, 1999) and localization signals (Conti, et al, 1998). Photocontrol of peptide activity is a powerful tool for precise spatial and temporal control of cellular function (Gautier, et al, 2010; Nguyen, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Peptides regulate a variety of biological processes by acting as competitive inhibitors (Singh, et al, 2005), allosteric regulators (Lockless and Ranganathan, 1999) and localization signals (Conti, et al, 1998). Photocontrol of peptide activity is a powerful tool for precise spatial and temporal control of cellular function (Gautier, et al, 2010; Nguyen, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These residues are structurally equivalent to Ser195 and Gly193, respectively, in chymotrypsin. Thus, the geometry of the catalytic triad and the oxyanion hole are well conserved among clan PA peptidases28293031 (Fig. 5).…”
Section: Resultsmentioning
confidence: 95%
“…The 14 amino acid long peptide turned out to have affinity for the active site of the enzyme. The X-ray diffraction data showed the peptide bound to the active site and the crystal was catalytically inactive [15]. Nevertheless, these observations also pointed out that TPP treated enzyme had a different conformation which was more vulnerable to autolysis during the long period of crystallization.…”
Section: Introductionmentioning
confidence: 95%
“…We had observed that TPP treatment of alpha chymotrypsin leads to a higher activity for the enzyme in both aqueous and low water media [10]. Unfortunately, our attempts at obtaining the structure of TPP treated alpha chymotrypsin by X-ray diffraction did not succeed [15]. During crystallization attempts, TPP treated alpha chymotrypsin underwent a selective autocatalytic cleavage near the N-terminus.…”
Section: Introductionmentioning
confidence: 97%